2016
DOI: 10.1039/c5ra21250b
|View full text |Cite
|
Sign up to set email alerts
|

A facile way to prepare nanoporous PbI2 films and their application in fast conversion to CH3NH3PbI3

Abstract: Nanoporous PbI2 films, prepared in a facile way, are applied to accelerate the reaction in the two-step deposition of CH3NH3PbI3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Both, a porous and a non‐porous structure, can have advantages for the fabrication of homogeneous perovskite films. On the one hand, a porous structure makes it easier to convert the MAPI film and leaves space for the volume expansion during the conversion . On the other hand, a structure that is too porous will leave gaps after conversion.…”
Section: The Relationship Between Precursor Morphology and Mapi Film mentioning
confidence: 99%
“…Both, a porous and a non‐porous structure, can have advantages for the fabrication of homogeneous perovskite films. On the one hand, a porous structure makes it easier to convert the MAPI film and leaves space for the volume expansion during the conversion . On the other hand, a structure that is too porous will leave gaps after conversion.…”
Section: The Relationship Between Precursor Morphology and Mapi Film mentioning
confidence: 99%
“…The latter work demonstrated that PbI 2 deposition proceeds via a sol–gel process whereby a disordered precursor solvate crystallizes into metastable PbI 2 ‐DMF co‐crystal phases which spontaneously convert to PbI 2 at room temperature. The observation that as‐cast PbI 2 films exhibit a complex and time‐dependent solvated states provides interesting opportunities to convert from solvent‐expanded and metastable precursors into the perovskite phase and thus access improved conversion and high‐quality perovskite films …”
Section: Introductionmentioning
confidence: 99%
“…24,27 The p-PbI 2 lms with a larger specic area can also facilitate its reaction with MAI because more reaction sites are provided, which is consistent with the previous literatures. 31,37 The corresponding absorption spectra of the prepared perovskite lms without and with annealing at 100 C for 30 min are shown in Fig. 2(c) and (d), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To address the PbI 2 residue issue for producing highperformance perovskite lms, some strategies have been developed. 8,[30][31][32][33][34][35] Recently, we demonstrated that the incorporation of polymer P(VDF-TrFE) into the PbI 2 precursor lm can achieve the complete conversion of PbI 2 to MAPbI 3 by retarding the crystallization of PbI 2 . 36 Gong et al 37 reported that the application of the mesoporous PbI 2 scaffolds, employing the nucleation and growth of PbI 2 crystallites in a wet lm, can be rapidly converted into perovskite lms without any PbI 2 residue.…”
Section: Introductionmentioning
confidence: 99%